2010
DOI: 10.3758/s13414-010-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

First come, first served? Influence of changed object configuration on object-based attention

Abstract: Evidence for object-based attention is based mainly on studies using object displays that remain unchanged throughout, with the assumption that object representation should be completed and stabilized before it is selected for further processing. We used the modified double-rectangle cuing paradigm of Egly, Driver, and Rafal (Journal of Experimental Psychology: General, 123, 161-177, 1994) but introduced a configuration change to the cued-object display to test whether object-based attention is determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
(54 reference statements)
2
6
0
Order By: Relevance
“…We previously proposed a dynamic-updating hypothesis to explain the results that an initially attended and then changed object affects object-based attention (Lin & Yeh, 2011). In the present study, we further demonstrated that the way that the boundary of an object is changed affects objectbased attention.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…We previously proposed a dynamic-updating hypothesis to explain the results that an initially attended and then changed object affects object-based attention (Lin & Yeh, 2011). In the present study, we further demonstrated that the way that the boundary of an object is changed affects objectbased attention.…”
Section: Discussionsupporting
confidence: 62%
“…Using the double-rectangle cuing paradigm (Egly, Driver, & Rafal, 1994), we previously showed that object-based attention operates on a dynamic representation: Object-based attentional guidance is affected by subsequent changes occurring to an attended object (Lin & Yeh, 2011). The present study provides further support for our dynamicupdating hypothesis, demonstrating that changes are indeed updated into the existing object representation.…”
supporting
confidence: 73%
See 3 more Smart Citations